Multi-choice mixed integer goal programming optimization for real problems in a sugar and ethanol milling company - da Silva, Aneirson Francisco [UNESP]; Silva Marins, Fernando Augusto [UNESP]; Barra Montevechi, José Arnaldo (Elsevier, 2013)
Goal Programming (GP) is an important analytical approach devised to solve many realworld problems. The first GP model is known as Weighted Goal Programming (WGP). However, Multi-Choice Aspirations Level (MCAL) problems cannot be solved by current GP techniques. In this paper, we propose a Multi-Choice Mixed Integer Goal Programming model (MCMI-GP) for the aggregate production planning of a Brazilian sugar and ethanol milling company. The MC-MIGP model was based on traditional selection and process methods for the design of lots, representing the production system of sugar, alcohol, molasses and derivatives. The research covers decisions on the agricultural and cutting stages, sugarcane loading and transportation by suppliers and, especially, energy cogeneration decisions; that is, the choice of production process, including storage stages and distribution. The MCMIGP allows decision-makers to set multiple aspiration levels for their problems in which the more/higher, the better and the less/lower, the better in the aspiration levels are addressed. An application of the proposed model for real problems in a Brazilian sugar and ethanol mill was conducted; producing interesting results that are herein reported and commented upon. Also, it was made a comparison between MCMI GP and WGP models using these real cases. © 2013 Elsevier Inc.
Keywords: Aggregate production planning; Goal programming; Multi- Choice mixed integer goal programming; Multi-choice aspiration levels; Sugar and ethanol mills; Analytical approach; Goal programming model; Multi choices; Multiple aspiration levels; Production process; Real-world problem; Aggregates; Ethanol; Industry; Integer programming; Loading; Milling (machining); Production engineering; Problem solving